Calidad del servicio de internet y satisfacción del cliente - Moreno Cardenas, Edison Yuver (2020)
The main objective was to identify the variation of the average of customer satisfaction in proportion to the average of Internet service quality. The population consisted of 13 corporate portfolio customers of Internet service provider América Móvil Perú S. A. C. Likewise, the variables used were quality of Internet service and customer satisfaction. The non-experimental correlational design was used for this purpose in the form of surveys, which provided results regarding the variation between the variables. The research obtained a result of 0.77, which indicates that there is a positive proportional variation between both variables. Furthermore, there is a high level of correlation and, when performing the analysis, the bilateral significance level was 0.000, less than 0.05. It is concluded that the average of Internet service quality varies in proportion to the average of customer satisfaction.